2009
DOI: 10.1002/adfm.200900357
|View full text |Cite
|
Sign up to set email alerts
|

Study of Energy Transfer and Triplet Exciton Diffusion in Hole‐Transporting Host Materials

Abstract: A device structure is used in which the hole‐transporting layer (HTL) of an OLED is doped with either fluorescent or phosphorescent emitters, that is, anode/HTL‐host/hole blocker/electron‐transporting layer/cathode. The HTL hosts have higher HOMO energy allowing holes to be transported without being trapped by dopant molecules, avoiding direct recombination on the dopant. The unconventional mismatch of HOMO energies between host and dopant allow for the study of energy transfer in these host/guest systems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 39 publications
(39 reference statements)
0
47
0
Order By: Relevance
“…Compound 4 showedo ne reversible oxidation wave at + 0.77 Vv s. the ferrocenium/ferrocene( Fc + /Fc) couple. In comparison, 5 displayed two well-defined one-electron reversible redox couples at + 0.37 and + 0.69 Vv ersus Fc + /Fc corresponding to 5/ 5 + C and 5 + C/5 2 + .T he oxidation potentials of 4 and 5 were anodically shifteda sc ompared with the reference compounds, [37,38] indicating that the HOMO energy levels were stabilized by the introduction of electron-accepting nitrile groups.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Compound 4 showedo ne reversible oxidation wave at + 0.77 Vv s. the ferrocenium/ferrocene( Fc + /Fc) couple. In comparison, 5 displayed two well-defined one-electron reversible redox couples at + 0.37 and + 0.69 Vv ersus Fc + /Fc corresponding to 5/ 5 + C and 5 + C/5 2 + .T he oxidation potentials of 4 and 5 were anodically shifteda sc ompared with the reference compounds, [37,38] indicating that the HOMO energy levels were stabilized by the introduction of electron-accepting nitrile groups.…”
Section: Resultsmentioning
confidence: 96%
“…/5 2+ . The oxidation potentials of 4 and 5 were anodically shifted as compared with the reference compounds, indicating that the HOMO energy levels were stabilized by the introduction of electron‐accepting nitrile groups.…”
Section: Resultsmentioning
confidence: 98%
“…In the case of the high triplet energy of mCP (408 nm, 3.04 eV) [16] and a small amount of phosphorescent molecules, it's reasonable to postulate that mCP interlayer plays a role not only as a spacer between two phosphorescent ultrathin layers but also as an emitter in the devices. From Fig.…”
Section: Resultsmentioning
confidence: 98%
“…29 As show in Fig. [19][20][21] Therefore, for these asymmetrical squaraine derivatives, the presence of N,N-diarylamino end-cappers could not endow them with better hole mobility. While for the six objective compounds, the hole mobility of their neat lms were calculated to be 0.56 Â 10 À5 to 5.42 Â 10 À5 cm 2 V À1 s À1 , and that of the composite lms is 0.44 Â 10 À5 to 1.77 Â 10 À5 cm 2 V À1 s À1 , both are comparable or even lower than that of ASQB samples.…”
Section: Hole Mobilitymentioning
confidence: 98%
“…16 Although ASQB displays a relatively low bandgap and good solubility owing to the presence of an electron-rich N,N-diisobutylamino group in it, the PCE of the corresponding BHJ-SMOSCs is unsatisfactory (1.54%), with low V oc of 0.75 V, J sc of 5.40 mA cm À2 , and FF of 0.38. 16 Moreover, recent research works have revealed that the replacement of N,Nalkylamino with N,N-diarylamino substituents in photovoltaic materials could not only lead to more intensied intermolecular p-p overlap that benets the broaden of the absorption spectra and the enhancement of charge-transporting properties in lm states, 19,20 hence higher J sc could be expected; but also endow these compounds with dropped HOMO energy levels, hence higher V oc could also be expected. 17,18 Additionally, by replacing the end-capper with a carbazolyl group, the resulting compound ASQC was found to show considerably lowered HOMO energy level, hence ASQC-based SMOSCs displays a very high V oc ; however, ASQC exhibits a higher energy bandgap with that of ASQB.…”
Section: Introductionmentioning
confidence: 99%